Evaluación del potencial turístico del Camino Histórico de los Hieleros como alternativa para el desarrollo dentro de la Ruta Sara Kapak Ñan en el cantón Guaranda, provincia Bolívar año 2019 - Chillo Cambo, Adriana Katerine (2019)
Today, tourism is considered one of the main sources of economic development in several countries of the world, as it integrates various activities that are environmentally friendly. The historic road of the icemakers within the Route of the Sara Kapak Ñan has several natural tourist attractions, which can be enjoyed if proper use is made of them under the guidelines of sustainable tourism. The inhabitants of the parish of Quindihua Central were engaged in the ice extraction of the snow-capped Chimborazo, an activity that left them with economic income to be able to subsist. Over the years, the ice-mining industry was lost because of the existence of refrigerators, prices were extremely low in order to compensate for any effort required to carry out this difficult task. In tourism there is a new hope to improve the economy of the community, thanks to the fact that this route has several tourist attractions such as: Vertiente Chaguakpukyo, Bosque Yanasacha, Cascada Gallo Cantana, Cascada del Diablo Tuso, Cascada de Oro, Horno de Inca Cal, Tinku Sagrado, Museo Comunitario. This research is the result of information obtained through a field study and the application of surveys. In this work they are considered as objectives: To evaluate the tourist potential of the Historic Path of the Ivleros within the route Sara Kapak Ñan, with the aim of tourism development and conservation, for sustainable management and proper use of resources by the people. Also carry out the socio-cultural, productive and environmental diagnosis of the area where the ancestral path is located. To inventory the natural and cultural heritage that generates the Camino Histórico de los Hieleros and to characterize the tourist demand with the determination to link the products and services to their preferences. Keywords Historic road, tourist potential, Sara Kapak Ñan